Representasi Komunikasi Interpersonal terhadap Psychological well-being Seseorang dalam Film Animasi "Soul" - Lisa Orellia; Nanang Ganda Prawira (ULTIMART Jurnal Komunikasi Visual, 2021)
The animated film Soul tells about a person who is experiencing symptoms of a midlife crisis who gets important lessons for his life from the people around him. This film shows how the meaning of one's existence and happiness can be influenced by the existence of other humans through communication. If viewed from the perspective of communication science it is a process of interpersonal communication. The purpose of this study is to determine the meaning of denotation, connotation, and myth that represent the concept of interpersonal communication so that it can affect a person's psychological well-being in the animated film Soul. This film will then be dissected using Roland Barthes' semiotic analysis technique. This research is a qualitative descriptive study with documentation studies as research data collection techniques. The results showed that the practice of interpersonal communication in the film Soul is represented by communication scenes performed by two to three people. This scene involves Joe as a middle-aged man, a new soul named 22 and Joe's friend Dez, a barber who explains that he is happy with his job even though his dream as a veterinarian is not fulfilled. He loves his job because he can hear every experience from his customers as he cuts Joe's hair, which is actually in that scene, the soul that resides inside Joe's body are 22. Keywords: semiotic analysis ; interpersonal communication ; animation.